2018
DOI: 10.3892/mmr.2018.9342
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and expression of ABCA12 in keratosis pilaris and nevus comedonicus

Abstract: Keratosis pilaris (KP) and nevus comedonicus (NC) are congenital keratinized dermatoses; however, the exact etiology of these two diseases is unclear. The objective of the present study was to identify the disease-causing genes and their association with functional alterations in the development of KP and NC. Peripheral blood samples of one KP family, two NC families and 100 unrelated healthy controls were collected. The genomic sequences of 147 genes associated with 143 genetic skin diseases were initially an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
5
0
5
Order By: Relevance
“…This particular form of ichthyosis was explained by the combination of a germline mutation and an acquired postzygotic mutation in this gene. ABCA12 gene was reported also in a keratosis pilaris with missense mutation and in Nevus comedonicus with a high protein expression level in the sebaceous gland without any variation in ABCA12 coding region [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This particular form of ichthyosis was explained by the combination of a germline mutation and an acquired postzygotic mutation in this gene. ABCA12 gene was reported also in a keratosis pilaris with missense mutation and in Nevus comedonicus with a high protein expression level in the sebaceous gland without any variation in ABCA12 coding region [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study concluded that fibrinogen alpha chain genes impact keratosis pilaris because it codes for amino acids that produce the profilaggrin protein, which contributes to keratin and acid levels of the skin [13,33].…”
Section: Results Of Treatment With Genetic Acidsmentioning
confidence: 99%
“…As previously stated, keratosis pilaris is a genetic condition; therefore, some of the genes producing amino acids can have some impact on keratosis pilaris. For example, fibrinogen alpha chain and guanine nucleotide exchange factor 1 genes code for amino acids that create proteins that have an effect on acne and hyperpigmentation [13,14]. However, this review generally focuses on steroids, kinase inhibitors, and types of acids that the majority of keratosis pilaris and other acne treatments consist of.…”
Section: Genetic Acidsmentioning
confidence: 99%
“…The prevalence has been found to be between 1 in 45,000 to 1 in 100,000. Genetic mosaicism plays a role in the etiology of nevus comedonicus (Liu et al, 2018;Levinsohn et al, 2016). Individual lesions are multiple aggregated papules with open comedo like lesions topped with black colored keratin plugs.…”
Section: Resultsmentioning
confidence: 99%